Test report no. PLBO/12: comparison of modified forms of PERPRO carbide grade TO 348 when machining EN 9 - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
Tools of TO 3)48/ RD60, RD61, RD62, RD63 and Standard were tested to 0.030 in. flankwear when machining EN 9 at 600 fpm with 0.010 in/rev. feed and 0.10 in. depth of cut. The results showed that while no one grade was outstanding RD61, RD62 and RD63 gave an all round better performance than the other two grades.